The occurrence of carcinoma of the rectum following ileoproctostomy for familial polyposis. - Watne, A L (1983)
Ileoproctostomy was performed in 32 patients (13 Female and 19 male), with polyposis coli ranging in age from 10 to 54 years. Seven patients (22%) developed cancer of the retained rectum with a median follow-up of 14 years. Two (20%) of ten patients, followed for 10 to 15 years, and three (50%) of six patients, followed for 15 to 20 years, developed rectal cancer. Rectal cancer developed in two of 14 patients who had their ileoproctostomy at 14 cm and in five of 18 patients who had their ileoproctostomy at a higher level, with a median followup of 7 and 11 years, respectively. Rectal cancer developed in two of 15 teenage patients undergoing ileoproctostomy and in nine of 17 patients aged 20 to 54 years. The present average ages of the two groups were 25 and 41 years, and the average age at which rectal cancer appeared was 40 years. Three of the patients who developed rectal cancer had numerous polypectomies over the years, and there was a tendency to develop tubulovillous and villous adenomas with a variable degree of atypia leading to carcinoma. One patient also showed a return to high levels of coprostanol and secondary fecal bile acids. Proctocolectomy, if acceptable, may be the treatment of choice; ileoproctostomy may mean that the patient eventually will undergo a proctectomy. The ileoanal endorectal pull-through procedure has a great deal to offer to these patients, and further study is necessary to evaluate this procedure.